Recent Developments in Film and Gas Research in Modified Atmosphere Packaging of Fresh Foods. Issue 13 (2nd October 2016) - Zhang, Min; Meng, Xiangyong; Bhandari, Bhesh; Fang, Zhongxiang
Abstract : Due to the rise of consumer's awareness of fresh foods to health, in the past few years, the consumption of fresh and fresh-cut produces has increased sturdily. Modified atmosphere packaging (MAP) possesses a potential to become one of the most appropriate technologies for packaging fresh and fresh-cut produces. The MAP has advantages of extending the shelf-life, preserving or stabilizing the desired properties of fresh produces, and convenience in handing and distribution. The success of MAP-fresh foods depends on many factors including types of fresh foods, storage temperature and humidity, gas composition, and the characteristics of package materials. This paper reviews the recent developments highlighting the most critical factors of film and gas on the quality of MAP fresh foods. Although the innovations and development of food packaging technology will continue to promote the development of novel MAP, concentrated research and endeavors from scientists and engineers are still important to the development of MAP that focuses on consumers' requirements, enhancing product quality, environmental friendly design, and cost-effective application.